Cooperative Learning in The English Language Learning: A Systematic Review. - Fauziyatul Uzma; Sri Sumarni (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
There are numerous methods for learning English, and cooperative learning tends to aid students in comprehending and identifying tactics that are engaging and simple to implement to attain mastery objectives. This research was aimed at exploring the potentials and challenges of the use of cooperative learning in the English language learning. Systematic review is employed in this research, a total number of 43 articles published between 2018 and 2023 were selected in this paper. The impacts of cooperative learning on the English education, have been determined through a review of relevant literature. Hence, the findings of the examined literature indicate that adopting cooperative learning in learning the English language has positive outcomes. Each integrated skill of the English language is positively affected by cooperative learning, and it is suggested that the use of cooperative learning as one of the 21st-century skills should be considered for the future teaching and learning of the English language.